The Personality Of Alisher Navai In “KHAMSA” - Zulayho Abdurahman (International Journal of Medical Sciences And Clinical Research, 2025)
The personality of Alisher Navoi and his activities as a statesman have always been studied alongside his creative potential. The primary sources for exploring the poet’s ideal character are his own works. This article highlights the figure of the poet based on the “Khamsa” epic. Special attention is given to the fakhriya (self-praise) passages within the poem.